The Potential of Biostimulants to Enhance the Growth of Kappaphycus alvarezii (Rhodophyta) Propagules - Fadilah, Siti; Septiana, Shinta; sumiarsih, Sumiarsih; Wulan, Dyah Retno; khaerudin, Khaerudin; Prama, Ega Aditya; Putri, Lala Priyantika Adinda (Sains Akuakultur Tropis : Indonesian Journal of Tropical Aquaculture, 2025)
Kappaphycus alvarezii is a globally significant tropical red seaweed renowned for its carrageenan content. While tissue culture is a valuable technique for enhancing seedling quality and stress resilience in vegetative propagation, it is time-consuming and costly. Biostimulants have demonstrated the potential to enhance plant growth. This study aimed to evaluate the potential of biostimulants in enhancing the growth of K. alvarezii propagules. Three different biostimulant products were tested: biostimulant A (amino acid-based), biostimulant B (bacteria-based), and biostimulant C (seaweed extract-based). Each biostimulant was applied at two different concentrations and compared to a negative control and a positive control. Artificial seawater enriched with PES and supplemented with biostimulants according to the treatment was used as the growth medium. Growth of K. alvarezii propagules was monitored weekly, with the primary parameters being propagule weight and specific growth rate. Growth medium quality was assessed by in situ pH measurements and ex situ nitrate and phosphate analyses. Fermented biostimulants negatively impacted growth by reducing the pH of the culture medium, while biostimulant B (photosynthetic bacteria) maintained a near-neutral pH and showed the most promising results, with treatment B2 displaying stable growth and treatment B1 achieving the highest specific growth rate at week 6. Though treatments A1 and A2 showed higher nitrate and phosphate concentrations, these did not correlate with improved growth, likely due to the low pH. While these findings suggest the potential of photosynthetic bacteria for K. alvarezii growth, further research is necessary to fully understand the underlying mechanisms and to develop strategies to overcome the limitations associated with the acidic nature of fermented biostimulants.